Interventions to prevent violence against women and girls globally: a global systematic review of reviews to update the RESPECT women framework - Avni Amin; Mary Ellsberg; Chelsea Ullman; Angela Bourassa; Shikha Chandarana; Flávia Dutra (BMJ Public Health)
Objective The field of violence against women and girls (VAWG) prevention research has rapidly advanced, with ample evidence now demonstrating that VAWG is preventable. The aim of this systematic review of reviews is to update the evidence that underpins the RESPECT women framework with the newest available evidence from 2013 onward.Methods Academic and non-academic databases were searched using terms related to VAWG prevention (January 2013–April 2022). Evaluations had to have a target population of women or girls aged 10 and older. Data were extracted from included reviews, and AMSTAR-2 was used to assess the risk of bias in systematic reviews. The primary outcome of interest was change in any form of VAWG, including physical, sexual and emotional intimate partner violence and sexual violence and harassment from non-partners, including child and adolescent sexual abuse.Results From the thousands of articles screened, 178 were included in this study. Six (3%) reviews focused on interventions that aim to strengthen relationship skills, 14 (8%) focused on empowerment of women and girls, 79 (44%) on services for survivors, 5 (3%) on poverty reduction, 16 (9%) on creating safe environments, 36 (20%) on preventing child and adolescent abuse and 22 (12%) on transforming gender attitudes, beliefs and norms. Little new evidence has emerged to meaningfully change the nature and strength of evidence for interventions related to relationship skills strengthening and poverty reduction. However, there is new evidence to reflect the effectiveness of select types of interventions across settings in the other five strategies.Conclusion Despite progress in VAWG prevention research, significant gaps in the evidence base persist. Further research is needed to explore intervention areas and marginalised populations in various contexts. Several programmatic approaches exhibiting efficacy in low-income and middle-income countries remain unexplored and unevaluated in high-income countries, and vice versa, warranting further adaptation and evaluation.